Clinical Characteristics of Hospitalized Pediatric Patients With Hypertensive Crisis—A Retrospective, Single-Center Study in China - Ba, Hongjun; Peng, Huimin; Xu, Lingling; Qin, Youzhen; Wang, Huisheng (Frontiers in Cardiovascular Medicine, 2022)
Background: A hypertensive crisis is a medical emergency that causes acute damage to multiple organs. However, the etiology, clinical features, and prognosis of hypertensive crisis in Chinese children remain relatively unknown. The purpose of this study was to analyze the clinical characteristics of pediatric hypertensive crisis patients from a single center in China. Methods: We analyzed data from 70 children with hypertensive crisis between January, 2000, and January, 2022. The patients were divided into two groups: those diagnosed with a hypertensive emergency (n = 46) and those diagnosed with hypertensive urgency (n = 24). Baseline etiologies and risk factors were compared between the two groups. The following data were collected and analyzed: age, sex, weight, height, family history of hypertension, blood pressure, clinical manifestations of hypertensive crisis, underlying causes, biochemical indicators, and antihypertensive drugs. Results: The major symptoms of hypertensive crisis were headache (n = 31, 44.29%), followed by visual symptoms (n = 15, 21.43%), and dizziness (n = 13, 18.57%). The leading underlying causes were renal disease (n = 34, 48.57%), followed by vascular disease (n = 11, 15.71%), essential hypertension (n = 9, 12.86%), oncological disease (n = 9, 12.86%), central nervous system disease (n = 3, 4.29%), endocrine and metabolic diseases (n = 2, 2.86%), and other (one case with lead poisoning, one case with histiocytosis). End-organ damage occurred in 46 patients with hypertensive crisis, including retinal damage (n = 20, 43.48%), brain damage (n = 19, 41.30%), heart damage (n = 15, 32.61%), and renal damage (n = 3, 6.52%). Hypertensive crisis was most common among children aged 7–12 years. Among children aged 13–18 years, hypertensive urgency was more common than hypertensive emergency. The incidence of dyslipidemia, elevated serum creatinine, and elevated uric acid did not differ significantly between the two groups. Most patients with hypertensive crisis need combined antihypertensive therapy (n = 60, 85.71%). There were no cases of mortality. Conclusions: Hypertensive crisis is caused by secondary diseases, especially renal disease and vascular disease, in the majority of pediatric patients. Combination therapy with antihypertensive agents and treatment of secondary etiology results in a good prognosis.